(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
An ethnobotanical study was carried out to identify ethnomedicinally important plants of Barisal district of Bangladesh, document their traditional uses, and determine the consensus factor among the Folklore Medicinal Practitioners (FMPs). A total of 106 ethnomedicinal species under 55 families have been identified from Barisal district, which are used for treating 51 ailments with 120 formularies. Among the species, herbs constituted 59%, shrubs 15% and tress 26% of the total. Leaf was found to be the most frequently utilized plant part (44.33%), and most of the medicines were prepared in the form of juice (36%). The Factor of Informants Consensus (FIC) value ranged from 0.622 to 0.951 and the highest FIC value was found in cut, wound and bleeding. The highly cited species for these ailments are Mikania cordata (Burn.f.) Robinson, Cynodon dactylon (L.) Pers. and Chrozophora tinctoria (L.) A. Juss. Citation frequency (Cf) ranged from 20.93 to 67.44, and 11 species were found to have over 50% of Cf value. Fidelity level (Fl) value ranged from 69 to 100% and 17 species attained 100% Fl value. Our findings could provide baseline data to establish a tie between the traditional health practitioners and scientific communities, and finding out potential bioactive compounds for novel drug discovery.